Nanomaterials for Sustainable Pollution Management - Majhi, Surekha; Das, Tanushree; Bhoi, Rodana; Das, Bikram Keshari (Science and Technology: Developments and Applications Vol. 3, 2025)
Nanomaterials have emerged as a promising solution for sustainable pollution management, addressing the growing environmental challenges caused due to air, water, and soil pollution. This chapter provides an integrated overview of the types and effects of environmental pollution, emphasizing their impacts on ecosystems and human health. Conventional remediation methods, while widely used, often lack efficiency and sustainability, necessitating advanced approaches. The chapter explores the types of nanomaterials, such as metal oxides, carbon-based materials, and nanocomposites, exploring their unique properties and the characterization techniques essential for understanding their functionality. Advanced nanotechnology-based methods, including adsorption and photocatalysis, are discussed, with a focus on their fundamental mechanisms. Adsorption depends on the high surface area and reactivity of nanomaterials to capture pollutants, while photocatalysis utilizes light-driven degradation for breaking down contaminants. Applications of nanomaterials in air, water, and soil remediation are highlighted, demonstrating their ability to remove heavy metals, organic pollutants, and airborne contaminants efficiently. The chapter also addresses the challenges of nanotechnology, including toxicity, cost, and regulatory concerns, while proposing future strategies to enhance eco-friendliness and scalability. Overall, it underscores the transformative potential of nanomaterials in developing sustainable and efficient pollution management systems.